IDENTIFIKASI JENIS JAHE-JAHEAN LIAR (ZINGIBERACEAE) DI KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG KECAMATAN KUBU KABUPATEN KUBU RAYA - Suriyanto, Ignasius; Dirhamsyah, M.; kandar, Is (Universitas Tanjungpura, 2016)
Zingiberaceae is the family of flowering plants commonly known by the people of Indonesia as the Jahe-jahean. This plant is widely used for many things such as spices, medicine, ornamental plants, cosmetic ingredients, beverage ingredients, hair tonic, etc. The aim of the study is to know the species diversity of wild ginger in Gunung Ambawang Protected Forest Area, Kubu Raya Regency, West Kalimantan. The method of the reseacrh used exploration and specimen colection with observation in the research areas. According to the research in the field was found 10 species of wild Gingers who belong to the 7 different generaon the transect.The species that dominated in all of transect are Elettaria surculosa (K. Schum.) B.L. Burt & R.M. Sm. and Globba atrosanguinea Teijsm.& Binn. Keywords :Gunung Ambawang, Wild Gingers, Zingiberaceae.